Khilâfah Discourse on Youtube: Hizbut Tahrir Indonesia Scholars’ Perspective - Waki Ats Tsaqofi; Makyun Subuki; Arif Zamhari (Buletin Al-Turas, 2022)
PurposeThis study aimed to reveal how Hizbut Tahrir Indonesia (HTI)’s scholars, Ismail Yusnto, Felix Siuw, dan Fatih Karim used Youtube as ideological battle. It focused on discussing how texts experienced bias in representing khilâfah and how HTI ustaz used Youtube as a means to scroll their ideology. MethodThe study was qualitative research that used the verbal data of khilâfah discourse uploaded on Youtube as the primary source. Collecting the data, the researchers observed the discursivity of khilâfah as the main theme of discourse presented by HTI’s scholars on their preaching in Youtube. In data analysis, the study applied Norman Fairclough’s critical discourse analysis. Results/FindingsThe study showed that the HTI’s scholars exploited the khilâfah discourse through intellectual and well-packaged ways, one of which was through interesting and innovative videos uploaded on Youtube. The concept of khilâfah conveyed massively by the HTI’s scholars, especially on Youtube led to a single understanding of the khilâfah using HTI’s perspective. ConclusionThere were discourses about the governmental system that can be implemented in a country; and khilâfah was one of alternative system to apply. Khilâfah was not a single system by which a country was said to be Islamic one because Islam does not specifically regulate the government system. Therefore, it is important for the government to invite moderate scholars to enliven the khilâfah discourse to present more comprehensive one.